PH salival e índice de placa bacteriana, en los niños de 6 a 10 años con asma, del Hospital Isidro Ayora de la ciudad de Loja periodo marzo-julio 2015 - Romero Cevallos, Luis Cristobal (2015)
This descriptive study, observational, analytical and cross, was to determine the salivary pH and plaque index in children 6 to 10 years with asthma, Isidro Ayora Hospital in the city of Loja March-July period 2015. Dental history was used as data collection instrument to assess the variable: plaque (O'leary index), also using radioactive strips, salivary pH levels in selected patients were analyzed. The collection instrument was applied to 27 pediatric patients diagnosed with asthma in the Department of Internal Medicine at the Isidro Ayora Hospital. The results showed that 88.89% of the population presented acid pH, 11.11% presented a normal pH. The 31.85% of patients tested had an index of bad plate. Establishing the relationship, the greater percentage of patients with bad hygiene index showed a 51.85% acid pH. Keywords: Salivary pH, O'leary index, bronchial asthma